Climate change impacts on ecosystem functioning: evidence from an Empetrum heathland - Jeffers, E; Bonsall, M; Watson, J; Willis, K (Wiley-Blackwell, 2012)
Summary: The extent to which plants exert an influence over ecosystem processes, such as nitrogen cycling and fire regimes, is stil largely unknown. It is also unclear how such processes may be dependent on the prevailing environmental conditions. Here, we applied mechanistic models of plant-environment interactions to palaeoecological time series data to determine the most likely functional relationships of Empetrum (crowberry) and Betula (birch) with millennial-scale changes in climate, fire activity, nitrogen cycling and herbivore density in an Irish heathland. Herbivory and fire activity preferentially removed Betula from the landscape. Empetrum had a positive feedback on fire activity, but the effect of Betula was slightly negative. Nitrogen cycling was not strongly controlled by plant population dynamics. Betula had a greater temperature-dependent population growth rate than Empetrum; thus climate warming promoted Betula expansion into the heathland and this led to reduced fire activity and greater herbivory, which further reinforced Betula dominance. Differences in population growth response to warming were responsible for an observed shift to an alternative community state with contrasting forms of ecosystem functioning. Self-reinforcing feedback mechanisms - which often protect plant communities from invasion - may therefore be sensitive to climate warming, particularly in arctic regions that are dominated by cold-adapted plant populations.